Investigation antiradical and antioxidative action dezapur in experements in vitro - Volkovoy, V. A.; Sevrukov, O. V.; Bereznykova, M. E.; Reshetniyk, N. V.; Fomina, G. P.; Karabut, L. V. (Journal of Education, Health and Sport, 2016)
Volkovoy V. A., Sevrukov O. V., Bereznykova M. E., Reshetniyk N. V., Fomina G. P., Karabut L. V. Investigation antiradical and antioxidative action dezapur in experements in vitro. Journal of Education, Health and Sport. 2016;6(6):291-299. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55501 http://ojs.ukw.edu.pl/index.php/johs/article/view/3579 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. UDC 615.275.4:616-36-002:616.127 investigation antiradical and antioxIDATIVE action Dezapur in experements in vitrO V. A. Volkovoy, O. V. Sevrukov, M. E. Bereznykova, N. V. Reshetniyk, G. P. Fomina, L. V. Karabut National University of Pharmacy, Kharkiv, Ukraine Abstract This article presents the results of a study of antiradical and antioxidative action a new chemical compound 1-fenetil-5,7-dihydro-1H-pirolo-[2,3-d]pyrimidine-2,4,6-trione (code name dezapur). Antiradical activity was investigated on model of interaction dezapur with a stable radical dyphenilpykrylgydrazyn (DPPH) by used method deoxyribose and conversion reaction of adrenalin in adrenochrom. The results showed that dezapur in 10-5 M concentration after 10 min reduces the concentration of DPPH on 25,7%, and after 120 minutes on 64,7%. The reference-compound mexidol within 12 hours did not reduce the concentration of DPPH. Antioxidative activity of dezapur was determined in a model system for the egg yolk lipoprotein inhibition of accumulation of products which react with 2-thiobarbituric acid (TBA-active products) as well as indicators of Fe2+-biochemiluminescence initiated. The results suggest that concentrations in the range dezapur 0,2-100,0 mkg/ml exhibits antioxidant properties inhibiting the formation of TBA-active products on 72,6-97,9%. The antioxidative activity determined by parameters of biochemiluminescence, dezapur exceed mexidol, reducing the area ratio of light sum reaction BCL in a wide range of concentrations. Studies in vitro on several models showed that dezapur has a high antiradical and moderate antioxidative activity. Key words: antiradical and antioxidative action, spectrophotometry, chemiluminescence (BCL), dezapur, mexidol. Исследование АНТИРАДИКАЛЬНОго и АНТИОКИСлительного Действия дезапура В опытАХ IN VITRO В. А. Волковой, А. В. Севрюков, М. Е. Березнякова, Н. В. Решетняк, Г. П. Фомина, Л. В. Карабут Национальный фармацевтический университет, Харьков, Украина Реферат В данной работе приведены результаты исследования антирадикального и антиокислительного действия нового химического соединения 1-фенетил-5,7-дигидро-1Н-пироло-[2,3-d]пиримидин-2,4,6-трион (условное название дезапур). Антирадикальную активность исследовали на модели взаимодействия дезапура со стабильным радикалом дифенилпикрилгидразином (ДФПГ) используя дезоксирибозный метод и реакцию превращения адреналина в адренохром. Результаты исследований показали, что дезапур в концентрации 10-5 M уже через 10 мин снижает концентрацию ДФПГ на 25,7%, а через 120 мин на 64,7%. Препарат сравнения мексидол на протяжении 12 часов не снижал концентрацию ДФПГ. Антиокислительную активность дезапура определяли в модельной системе липопротеинов яичного желтка за угнетением накопления продуктов, которые реагируют с 2-тиобарбитуровой кислотой (ТБК-активные продукты) а также за показателями Fe2+-инициированной биохемилюминесценции. Полученные результаты свидетельствуют о том, что дезапур в диапазоне концентраций 0,2-100,0 мкг/мл проявляет антиокислительные свойства угнетая образование ТБК-активных продуктов на 72,6-97,9 %. За антиокислительной активностью, определенной по параметрам биохемилюминесценции, дезапур превышал мексидол, уменьшая показатель площади светосуммы реакции БХЛ в более широком диапазоне концентраций. Проведенные исследования in vitro на нескольких моделях показали наличие у дезапура високой антирадикальной и умеренной антиокислительной активности. Ключевые слова: антирадикальное и антиокислительное действие, спектрофотометрия, биохемилюминисценция (БХЛ), дезапур, мексидол. ДОСЛІДЖЕННЯ АНТИРАДИКАЛЬНОї і АНТИОКИснювальної Дії дезапура В дослідАХ IN VITRO В. А. Волковий, А. В. Севрюков, М. Е. Березнякова, Н. В. Решетняк, Г. П. Фоміна, Л. В. Карабут Національний фармацевтичний університет, Харків, Україна Реферат В даній роботі приведені результати дослідження антирадикальної і антиокиснювальної дії нової хімічної сполуки 1-фенетил-5,7-дигідро-1н-піроло-[2,3-d]піримідин-2,4,6-трион (умовна назва дезапур). Антирадикальну активність досліджували на моделі взаємодії дезапура зі стабільним радикалом дифенилпікрилгідразином (ДФПГ), використовуючи дезоксирибозний метод і реакцію перетворення адреналіну в адренохром. Результати досліджень показали, що дезапур в концентрації 10-5 M вже через 10 хв знижує концентрацію ДФПГ на 25,7%, а через 120 хв на 64,7%, препарат порівняння мексидол на протязі 12 годин не знижував концентрацію ДФПГ. Антиокиснювальну активність дезапуру досліджували у модельній системі ліпопротеїнів яєчного жовтка за пригніченням накопичення продуктів, які реагують з 2-тіобарбітуровою кислотою (ТБК-активні продукти), а також за показниками Fe2+-ініційованої біохемілюмінісценції. Одержані результати свідчать про те, що дезапур в діапазоні концентрацій 0,2-100,0 мкг/мл проявляє антиокиснювальні властивості пригнічуючи утворення ТБК-активних продуктів на 72,6-97,9 %. За антиокиснювальною активністю, визначеною за параметрами біохемілюмінесценції, дезапур перевершував мексидол, зменшуючи показник площі світлосуми реакції БХЛ, в більш широкому діапазоні концентрацій. Проведені дослідження in vitro на декількох моделях показали наявність у дезапура високої антирадикальної і помірної антиокиснювальної активності. Ключові слова: анти радикальна та антиокиснювальна дія, спектрофотометрія, біохемілюмінісценція (БХЛ), дезапур, мексидол.